1993
DOI: 10.1148/radiology.187.3.8497637
|View full text |Cite
|
Sign up to set email alerts
|

Anterior translocation of the tibia at MR imaging: a secondary sign of anterior cruciate ligament tear.

Abstract: The authors evaluated measurement of the degree of anterior subluxation ("translocation") of the tibia in regard to the femur as a predictor of anterior cruciate ligament (ACL) tear. Eighty-nine magnetic resonance (MR) imaging studies of patients with either an arthroscopically confirmed intact (n = 29), acutely torn (n = 27), or chronically torn (n = 33) ACL were retrospectively reviewed. The degree of translocation was measured on hard-copy images by using two methods. Buckling of the posterior cruciate liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 0 publications
1
58
0
4
Order By: Relevance
“…It was found that measuring ATS is an accurate way to diagnose rupture of the ACL and that there is a positive correlation with the duration of ACL deficiency [7,8,17].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that measuring ATS is an accurate way to diagnose rupture of the ACL and that there is a positive correlation with the duration of ACL deficiency [7,8,17].…”
Section: Discussionmentioning
confidence: 99%
“…Tibial subluxation has also been correlated with ACL rupture in diagnostic MRI scans acquired when subjects were supine, relaxed, and in full knee extension. 26 Comparison of goniometer linkage-based studies to medical imaging-based studies such as the current one should be evaluated in this knowledge. Measurement error can also be introduced by relative motion between goniometer linkages and bones during motion.…”
Section: Discussionmentioning
confidence: 99%
“…The PCL curvature value is defined as the length of line ªaº divided by the length of line ªb.º In cases of a normal ACL the value is 0.27 0.06 and for torn ACL 0.40 0.12 [13]. Anterior translocation of the tibia in ACL tear is defined when the distance of the posterior cortex to a line at the midlateral femoral condyle parallel to the edge of the image is greater than 5 mm [14,15]. The posterior horn of the lateral meniscus is uncovered when a vertical line drawn tangent to the posterior cortical margin of the lateral tibial plateau intersects any part of the posterior horn of the lateral meniscus [13].…”
Section: Anterior Cruciate Ligament Rupturementioning
confidence: 99%